Colorimetric detection of chloroperoxyl radical in reactive chlorine species solutions - Hiroyuki Kawata; Shunsuke Odai; Hisataka Goda; Yuki Okawa; Toshiaki Kamachi (PLoS ONE, 2025)
Chlorous acid water (CAW) is a chlorine-based disinfectant approved as a food additive in Japan. CAW is synthesized by the reaction of chloric acid aqueous solution with hydrogen peroxide under acidic conditions. However, in this synthesis method, various ions — such as Na + from NaClO 3 and the conjugate base of the acid used — remain in the solution, hindering the selective detection and decreasing stability of chloroperoxyl radical (ClOO•), a potential key disinfectant species. In this study, we aimed to establish a colorimetric quantification method for ClOO•. We prepared a high-purity ClOO• solution (ClO 2_cx ) by cation exchange and its purity and stability were evaluated using electron spin resonance (ESR) spectroscopy and total chlorine concentration measurements. Furthermore, several colorimetric methods—including DPD, TMB, and DPPH assays—were examined to quantify ClOO•, and their sensitivity and selectivity were comparatively assessed. ClOO• was the sole detectable oxidant in the solution, with a lifetime exceeding 100 h, indicating exceptional stability under ambient conditions. Among the evaluated colorimetric methods, the DPD-based method was found to be suitable for quantifying ClOO•, showing a wide detection range and excellent linearity. This study represents the first report of a colorimetric quantification method for ClOO•. Our findings are expected to be useful for quantitatively discussing the biological efficacy of ClOO• and its reaction mechanisms.